2007
DOI: 10.1007/s11764-007-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Health and supportive care needs of young adult cancer patients and survivors

Abstract: Needs of adolescents and young adults with cancer vary along a continuum of care, from diagnosis and treatment through survivorship. Findings emphasize the value of age-appropriate resources and peer support. The study offers direction for delivering services to what previously has been an underserved population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 46 publications
7
125
1
2
Order By: Relevance
“…These findings, that the majority of survivors do not have unmet needs, are consistent with other UK studies [12,[17][18]. There is, however, variation between unmet need levels across countries [11,[13][14][15][16]. This may be due partly to different health systems and possibly to cultural factors.…”
Section: Predictors Of Health and Wellbeingsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings, that the majority of survivors do not have unmet needs, are consistent with other UK studies [12,[17][18]. There is, however, variation between unmet need levels across countries [11,[13][14][15][16]. This may be due partly to different health systems and possibly to cultural factors.…”
Section: Predictors Of Health and Wellbeingsupporting
confidence: 90%
“…These studies however are limited methodologically and there are no studies that have been undertaken in Northern Ireland or in the Republic of Ireland. Furthermore, there is inconsistent evidence available regarding the prevalence of unmet need [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in southeast of Asia showed that family members are the main source of support for survivors (Cheng et al, 2013;You and Lu., 2014). Whereas, the results of Western studies showed that both family members and friends are the main resources for support for cancer survivors (Zebrack et al, 2007;Corey et al, 2008;Forsythe et al, 2014). Interestingly, unlike these studies, participants of the present study reported that they receive low levels of support from their friends.…”
Section: Discussioncontrasting
confidence: 68%
“…One such study from the United States reported that older young adults expressed a need for improved age-appropriate information and support (such as fertility options and psychological counseling) and that younger respondents wanted treatment options that least interfered with their lifestyle 13 . General health and wellbeing, sexuality, and a lack of social support have been cited as important issues for young adults, but are often poorly understood during cfc in this population 14 .…”
Section: Discussionmentioning
confidence: 99%